Bird collisions at an offshore platform in the North Sea. Issue 1 (2nd January 2016) - Hüppop, Ommo; Hüppop, Kathrin; Dierschke, Jochen; Hill, Reinhold
Abstract : Capsule Collisions with offshore structures in the North Sea could account for the mortality of hundreds of thousands of nocturnally migrating birds. Aims To assess, for the first time, the circumstances of mass fatalities at an offshore structure, including the species involved, their numbers, ages, body conditions and injuries. Methods At an unmanned tall offshore research platform in the southeastern North Sea, bird corpses were collected on 160 visiting days from October 2003 to December 2007. Corpses were identified to species and kinds of injury, ages, and fat and muscle scores were determined. Nocturnal bird calls were recorded, identified to species and quantified. Local and large-scale weather parameters were also considered. Results A total of 767 birds of 34 species, mainly thrushes, European Starlings and other passerines, were found at 45 visits. Most carcasses were in good body condition and young birds were not more affected than adults. Three quarters of 563 examined individuals had collision induced injuries. Birds in poor body condition were less likely to be collision victims than those in good condition. Mass collision events at the illuminated offshore structure coincided with increasingly adverse weather conditions and an increasing call intensity of nocturnal birds. Conclusions Assuming an average of 150 dead birds per year at this single offshore structure and additionally assuming that a considerable proportion of the corpses were not found, we estimate that mortality at the 1000 + human structures in the North Sea could reach hundreds of thousands of birds. Since offshore industrialization will progress and collision numbers at offshore turbines will consequently increase considerably, we recommend reinforced measures to reduce bird strikes at offshore structures, especially in the light of substantial declines in some migrant species.